2015
DOI: 10.1016/j.ijggc.2015.07.029
|View full text |Cite
|
Sign up to set email alerts
|

Influence of geochemical processes on the geomechanical response of the overburden due to CO2 storage in saline aquifers

Abstract: a b s t r a c tThe objective of the study is to investigate the influence of geochemical processes on the geomechanical response of overburden during and after CO 2 injection. In the current study, coupled multiphase fluid flow and geomechanical modeling with geochemical processes were performed to simulate large-scale injection of CO 2 (up to 10 million metric tonnes per year) into a deep saline aquifer over the long-term (up to 1000 years). The geochemical modeling results show that geochemical processes, su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 134 publications
(257 reference statements)
2
18
2
Order By: Relevance
“…Looking at these figures, it was observed that at the end of the injection periods in both aquifers, ground displacement is quantitatively different but very high near the wellbore region due to the pressure buildup as highlighted by Shi et al 12 As time passes and in the postinjection period, there is a continuous decline in the ground displacement, which is more pronounced in limestone. This contradicts the finding presented by Varre et al 2 where it was highlighted that calcite has an insignificant influence on the geochemical activity and vertical ground displacement of limestone. Likewise, another study by Hangx et al 52 showed the complete dissolution of calcite in sandstone upon chemical interaction of CO 2 without any effect on the mechanical properties.…”
Section: Geochemical and Geomechanical Assessmentscontrasting
confidence: 86%
See 2 more Smart Citations
“…Looking at these figures, it was observed that at the end of the injection periods in both aquifers, ground displacement is quantitatively different but very high near the wellbore region due to the pressure buildup as highlighted by Shi et al 12 As time passes and in the postinjection period, there is a continuous decline in the ground displacement, which is more pronounced in limestone. This contradicts the finding presented by Varre et al 2 where it was highlighted that calcite has an insignificant influence on the geochemical activity and vertical ground displacement of limestone. Likewise, another study by Hangx et al 52 showed the complete dissolution of calcite in sandstone upon chemical interaction of CO 2 without any effect on the mechanical properties.…”
Section: Geochemical and Geomechanical Assessmentscontrasting
confidence: 86%
“…The magnitude of vertical displacement obtained for the sandstone in this study is aligned with the results presented by Varre et al,2 where a sandstone formation with 76% quartz was simulated for 200 years. For the limestone aquifer, on the other hand, the results obtained were very close to what was reported by Kim et al50 and Masoudi et al, …”
supporting
confidence: 91%
See 1 more Smart Citation
“…HCO 3 -combined with positive ion in water solution as shown in Equations (7) and (8). Subsequently, bicarbonate and carbonate ions collided with divalent cation, they formed carbonate (Equations (9)(10)(11)(12) …”
Section: Variation Of Ion Contentmentioning
confidence: 99%
“…Fluid seepage mainly occurs through natural cleats or fractures, the interaction of minerals with CO 2 and groundwater significantly affects the flow characteristics of coal reservoirs [10]. Various studies on the mechanism of CO 2 -water-rock interactions have been conducted [11][12][13][14], the role of acidification to rock minerals through CO 2 injection, with the huge potential for CO 2 storage, was identified in saline aquifers and depleted oil and gas reservoirs. Considering its successful use in the oil and gas extraction industry, the acidizing approach was utilized for CBM recovery.…”
Section: Introductionmentioning
confidence: 99%